Screening of antiproliferative activity of artocarpus sp. towards hela cell line and caov-3 cell line - Khairun Nisa, Ibrahim Asri (Universiti Sains Malaysia, 2009)
Artocarpus sp. has been used as traditional folk medicine in Southeast Asia for treating ulcer, abscess, and diarrhea. This species also been reported to be used for treatment of inflammation, and malarial fever. In this study, three Artocarpus sp. extract were used to treat two types of cancer cell lines that are cervical cancer cell line (HeLa) and ovarian cancer cell line (CaOv-3) to screen the antiproliferative activity. The lowest (the best IC50 value) for inhibitory concentration at 50% of cells population (IC50) shows 6.3lJ.1g/mL. Treatment of CaOv-3 with Artocarpus extract with the lowest ICso value at specific incubation time that is 24 hr, 48hr, and 72hr resulted in inducing apoptosis have been determined by Hoechst stain. Result showed the DNA fragmentation event in the treated cells compared to untreated cells. Treatment of normal cell line, MDCK with the Artocarpus extract with the lowest IC50 value showed no cytoselective effect in the extract. However the extract inhibits cell growth at high concentration equal to I OJ.lg/mL. These results proposed that Artocarpus sp.exhibit antiproliferative activity on HeLa and CaOv-3 which inducing apoptosis in CaOv-3 cells.